Hedysarum marashicum (Fabaceae), a new species from Turkey - Ertuğrul, Tuğba; Fi̇şne Ahter; Ateş, Mevlüde Alev; Bağ, Ecem (Phytotaxa, 2025)
Hedysarum marashicum T. Ertuğrul & E. Bağ is described as a new species from Osmanoğlu Plateau in Afşin, Kahramanmaraş Province, Turkey. The new species differs from Hedysarum erythroleucum Schott & Kotschy ex Boiss. in loosely adpressed sericeous, greenish appearance (vs. densely adpressed sericeous, greyish-whitish appearance); branched near the base and 4–5 cm long stem (vs. not branched and absent or very short stem); longer stipule (7–10 mm vs. 3 mm); bigger obovate–oblong, 8–12 × 4–6 mm, densely sericeous whitish below and sparsely sericeous greenish above leaflets (vs. smaller ovate–rounded, 4–7 × 3–4 mm, very densely sericeous whitish on both surfaces leaflets); longer peduncle (10–15 cm vs. 3–10 cm); longer bract and bracteole (5–7 mm and 4–5 mm vs. 3 mm and 1–2 mm); bigger calyx 8–9 mm long (vs. calyx 5–8 mm long); bigger and bright pink corolla (vs. intensely purple corolla); densely pubescent pods (vs. pilose pods). Taxonomic descriptions, an identification key, palynology, fruit and seed morphology, phylogeny, the IUCN threat category, and figures for the new species were presented. Furthermore, the mapping of the geographical distribution of H. marashicum and H. erythroleucum was included.